Leading the learning revolution the expert's guide to capitalizing on the exploding lifelong education market - Cobb, Jeff (AMACOM, 2013)
Explains how to get involved in the continuing adult education industry, covering such topics as creating business models for the online learning landscape, promoting content, creating an action plan, and converting prospects to customers.